Poems in the Menggala Wedding Tradition - Iqbal Hilal; Munaris; Muharsyam Dwi Anantama; Rahmat Prayogi (Jurnal IKADBUDI, 2025)
The art of poetry is one of the unique cultural heritages of the people of Menggala Regency. Initially, this oral tradition of art was a form of expression of someone's feelings which was processed in the form of artistic performances. Poetry art thrives in various areas of Lampung, including Krui, South Lampung, Tanggamus, Central Lampung and North Lampung. Each region has its own unique rhythm. Poetry is a form of literature that is conveyed orally, usually through speech or live performance. The content of the poetry can be in the form of advice, criticism, aspirations, or expressions of joy. This research was carried out because proficiency in the art of such poetry is very rare. The aim of this research is to revive people's skills regarding the art of poetry which has almost become extinct. The research method used is descriptive qualitative with data collection techniques through observation and literature study. The results of the research show that the oral tradition of poetry functions as an artistic and cultural medium that connects the older generation with the younger generation or between society and the government to convey aspirations, suggestions, criticism or expressions of happiness. Several efforts have been made to preserve, utilize and develop this poetry art through schools, galleries and traditional art festivals.